SALICYLIC ACID-INDUCED IMPROVEMENT IN GERMINATION AND GROWTH PARAMETERS OF WHEAT UNDER SALINITY STRESS - J. Fardus; M. A. Matin; M. Hasanuzzaman; M. A. Hossain; M. Hasanuzzaman (Journal of Animal and Plant Sciences, 2018)
A pot experiment was conducted at the experimental shed of the Department of Agronomy, Sher-e-Bangla Agricultural University, Bangladesh during in winter season (2013-2014) with a view to find out the regulatory roles of exogenous salicylic acid (SA) in germination and growth of wheat under salt stress condition. The experiment was carried out with two varieties i.e. BARI Gom 21 and BARI Gom 25 and ten salt stress treatments viz. control (without salt), SA (1 mM salicylic acid), S50 (50 mM NaCl), S50+SA (50 mM NaCl with  1 mM SA), S100 (100 mM NaCl), S100+SA (100 mM NaCl with 1 mM SA), S150 (150 mM NaCl), S150+SA (150 mM NaCl with 1 mM SA), S200 (200 mM NaCl) and S200+SA (200 mM NaCl with 1 mM SA). Seed germination percentage, normal seedling percentage, length of shoot and root, fresh weight of shoot and root and dry weight were decreased under the stress condition but the abnormal seedling percentage increased. Salt stresses significantly reduced the plant height, tillers hill-1, fresh weight and dry weight of both varieties at all growth duration. Exogenous SA application with salt stress improved germination and crop growth parameters in both cultivars where BARI Gom 25 showed better tolerance. But, SA application could not improve germination and crop growth parameters at extreme level of salt stress (200 mM NaCl).
Keywords: Abiotic stress; Phytohormones; Salinity; Seed germination